2015
DOI: 10.1039/c4nj01332h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high surface area mixed metal oxide from the NiMgAl LDH precursor for nitro-aldol condensation reaction

Abstract: NiMgAl mixed oxide catalyzes nitro-aldol condensation reaction at room temperature under solvent free conditions exhibiting 99% conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 60 publications
0
17
1
Order By: Relevance
“…The thermal stability of lutein/LDH composites was evaluated by comparing with the degradation temperature of lutein presented in the thermogravimetric analysis and differential scanning calorimetry (TGA-DSC) curves. Different from most previous reports, the LDH decomposition was complete below 600 • C including two characteristic stages of mass loss [60][61][62], there was three-step mass loss of prime LDH from room temperature to 800 • C corresponding to four endothermic peaks. As presented in Figure 3a, the mass loss of the first stage between 70 and 220 • C could be ascribed to the removal of physically adsorbed and interlayer H 2 O.…”
Section: Characterization Of Lutein/ldh Compositescontrasting
confidence: 83%
“…The thermal stability of lutein/LDH composites was evaluated by comparing with the degradation temperature of lutein presented in the thermogravimetric analysis and differential scanning calorimetry (TGA-DSC) curves. Different from most previous reports, the LDH decomposition was complete below 600 • C including two characteristic stages of mass loss [60][61][62], there was three-step mass loss of prime LDH from room temperature to 800 • C corresponding to four endothermic peaks. As presented in Figure 3a, the mass loss of the first stage between 70 and 220 • C could be ascribed to the removal of physically adsorbed and interlayer H 2 O.…”
Section: Characterization Of Lutein/ldh Compositescontrasting
confidence: 83%
“…Thus, the precipitated M(OH) 2 and MCO 3 were formed by the deposition method, suggesting that the calcination‐induced decomposition of the fresh LDHs samples increased their porosity and surface area by releasing H 2 O or CO 2. This indicates that the deposition method enhances the surface area of the sorbents. Samples containing Zn and Mn exhibited the highest improvement in their surface area.…”
Section: Resultsmentioning
confidence: 92%
“…Herein, the focus will be given to the effects of different thermal temperatures on the LDH precursors. Barali et al reported on the conversion of ternary NiMgAl-LDH into MMO at the optimal temperature of 450 C. 70 They revealed that the temperature below 350 C results in no characteristic change in the layered structure of LDH, suggesting no formation of MMO. Besides, it leads to lower photocatalytic activity and BET surface of 584 m 2 g À1 .…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Lower thermal stability of LDH easily converts them into MMO under heat supply by removing the OH groups at the interlamellar space. 70 Making up the brucite layer of LDH is Mg 2+ occupying the tetrahedral sites and Cr 3+ filling up the octahedral site. The integration of diversified Mg 2+ and Cr 3+ leads to higher valency of the multimetal centers, reducing the activation energy for electron transfer between the cations.…”
Section: Mg-based Ldhmentioning
confidence: 99%